13C-NMR-based MixONat strategy coupled with 2D NMR for rapid dereplication and identification of new secondary metabolites from Aloe vera - Yin, T.; Yu, Y.; Liu, Q.; Zhu, G.; Bai, L.; Zhang, W.; Jiang, Z.
Aloe vera, the most popular and widely cultivated Aloe (Liliaceae)species, is receiving widespread and increasing attention from the food industry due to its functional and health benefits. The discovery of multitype metabolites from A. vera supported and broadened its application as a functional food. NMR-based dereplication methodology represents an efficient strategy in plant metabolite research. In the present study, by using the 13C NMR-based dereplication software MixONat along with a specially constructed Aloe database containing predicted 13C NMR chemical shifts for Aloe-derived natural products, the secondary metabolites in semipurified fractions from A. vera were rapidly identified. A total of twenty-one components (1-21), represented by chromones and anthraquinones, were identified in A. vera, and five of these (4, 14, 16, 18, and 21)were found in the Aloe genus for the first time. Moreover, two new chromones (1-2)were discovered by 2D NMR spectral analysis, and their structures were finally established by extensive spectroscopic analysis after targeted isolation. The results demonstrated that A. vera is a promising natural source of bioactive components and supported its broad utilization in the food industry. Moreover, the NMR-based dereplication approach was demonstrated to be a powerful tool for exploring secondary metabolites from edible plant resources.
Keywords: ALOE VERA; DEREPLICATION; NMR; CHROMONE